Mujer caminando por la zona baja de Belén - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: The photograph shows a woman walking through the lower part of Belen, in the background of the photo, the Glorieta de Belen and people at their rustic material stalls.
ENGLISH: La fotografía muestra a una mujer caminando por la zona baja de Belén, en el fondo de la foto, la Glorieta de Belén y gente en sus tenderetes de material rústico.

SPANISH: The photograph shows a woman walking through the lower part of Belen, in the background of the photo, the Glorieta de Belen and people at their rustic material stalls.
ENGLISH: La fotografía muestra a una mujer caminando por la zona baja de Belén, en el fondo de la foto, la Glorieta de Belén y gente en sus tenderetes de material rústico.
Woman walking in the lower area of Belen
Keywords: Iquitos (Perú)|~|Mujeres Loretanas|~|Perú--Cultura|~|Perú--Cultura Amazónica